Plasmid-Cured Chlamydia caviae Activates TLR2-Dependent Signaling and Retains Virulence in the Guinea Pig Model of Genital Tract Infection - Frazer, Lauren C.; Darville, Toni; Chandra-Kuntal, Kumar; Andrews, Jr, Charles W.; Zurenski, Matthew; Mintus, Margaret; AbdelRahman, Yasser M.; Belland, Robert J.; Ingalls, Robin R.; O'Connell, Catherine M. (PLOS ONE, 2012)
Loss of the conserved “cryptic” plasmid from C. trachomatis and C. muridarum is pleiotropic, resulting in reduced innate inflammatory activation via TLR2, glycogen accumulation and infectivity. The more genetically distant C. caviae GPIC is a natural pathogen of guinea pigs and induces upper genital tract pathology when inoculated intravaginally, modeling human disease. To examine the contribution of pCpGP1 to C. caviae pathogenesis, a cured derivative of GPIC, strain CC13, was derived and evaluated in vitro and in vivo. Transcriptional profiling of CC13 revealed only partial conservation of previously identified plasmid-responsive chromosomal loci (PRCL) in C. caviae. However, 2-deoxyglucose (2DG) treatment of GPIC and CC13 resulted in reduced transcription of all identified PRCL, including glgA, indicating the presence of a plasmid-independent glucose response in this species. In contrast to plasmid-cured C. muridarum and C. trachomatis, plasmid-cured C. caviae strain CC13 signaled via TLR2 in vitro and elicited cytokine production in vivo similar to wild-type C. caviae. Furthermore, inflammatory pathology induced by infection of guinea pigs with CC13 was similar to that induced by GPIC, although we observed more rapid resolution of CC13 infection in estrogen-treated guinea pigs. These data indicate that either the plasmid is not involved in expression or regulation of virulence in C. caviae or that redundant effectors prevent these phenotypic changes from being observed in C. caviae plasmid-cured strains.